Characterization, biochemical defense mechanisms, and antifungal activities of chitosan nanoparticle-encapsulated spinach seed essential oil - Hajar Soleimani; Reza Mostowfizadeh-Ghalamfarsa; Mustafa Ghanadian (Journal of Agriculture and Food Research, 2025)
Contemporary plant protection is progressively turning to non-chemical approaches. This study involved preparing spinach seed essential oil (SSEO)-loaded in chitosan nanoparticles (SSEO-LCNPs) as a delivery system, identifying the SSEO components, and evaluating their antifungal efficacy against Podosphaera fusca, the causative agent of powdery mildew in cucumber. Zeta potential, field emission scanning electron microscopy (FESEM), and dynamic light scattering (DLS) assessments were used to characterize the structural, physical, and chemical characteristics of the SSEO-loaded chitosan nanoparticles. Gas Chromatography-Mass Spectrometry analysis of SSEO revealed the presence of aromadendrene, L-limonene, and trans-anethole as the predominant components. Characterization of the SSEO-LCNPs revealed a spherical morphology, an average diameter of 116.2 nm, and a surface that is negatively charged, with an average zeta potential of −27.7 mV. The highest encapsulation efficiency and loading capacity of the essential oil were achieved with a 1:1 chitosan-to-SSEO weight ratio. The behavior of SSEO release from nanoparticles was effectively characterized by the Korsmeyer-Peppas model. Foliar application of 400 μg mL−1 SSEO-LCNPs significantly reduced the severity of powdery mildew in cucumber in greenhouse-grown seedlings. Compared to untreated controls, SSEO-LCNP treatment significantly increased phenolic and flavonoid levels; and peroxidase, polyphenol oxidase, and phenylalanine ammonia-lyase activities in cucumber leaves, regardless of P. fusca inoculation. Our study illustrated a significant positive correlation between defense mechanism responses induced by SSEO-LCNP in P. fusca-infected cucumber seedlings. The combined antifungal and plant defense-inducing properties of SSEO-LCNPs in combating the pathogen highlight their potential for developing the next generation of plant control agents aimed at promoting sustainable agricultural strategies to manage cucumber powdery mildew.